Effect of tacrolimus formulation on neurocognition in older kidney transplant recipients: A randomized controlled trial - Hadia Lala Gul; Macey Sockolov; Katherine Howes; Amanpreet Kaur; Michelle Occhipinti; Heejung Bang; Muna Alnimri; Yihung Huang; Joy Dray; Ling-Xin Chen (Transplantation Reports)
Background: Tacrolimus is known to cause neurotoxicities that may be more severe in older individuals. We aimed to compare the neurocognitive side effects of immediate release (IR) and LCP tacrolimus in older kidney transplant recipients in the early post-transplant period. Methods: In this single center, open-label, randomized and controlled trial of 64 kidney transplant recipients aged 60 or above, participants were randomized to LCP tacrolimus or IR tacrolimus between 4- and 8-weeks post-transplantation and followed for 6-weeks. The primary outcome of neurocognitive performance at 6-weeks compared with baseline was assessed by the Montreal Cognitive Assessment (MoCA) and Digit Symbol Substitution Test (DSST). Secondary outcomes included health-related quality of life as measured by the Quality of Life in Essential Tremor Questionnaire (QUEST) and Organ Transplant Symptom and Wellbeing Instrument (OTSWI). Results: 32 patients were randomized to IR tacrolimus and 31 to LCP tacrolimus. In the IR tacrolimus arm, the MOCA score increased by 1.2 points (SD 2.1) and the DSST score increased by 1.0 points (SD 7.8). In the LCP tacrolimus arm, the MOCA score increased by 0.2 points (SD 2.9) and the DSST score increased by 1.3 points (SD 7.5). No statistically significant difference was detected between arms in MOCA, DSST, QUEST or OTSWI scores. There was a trend toward improvement in tremor severity in the LCP tacrolimus arm. Conclusions: No improvement was found in MoCA or DSST performance in patients switched to LCP tacrolimus as compared to IR tacrolimus after 6 weeks of exposure in the early post-transplant period.